Propionibacterium acnes Causing Mediastinal Infection following Endobronchial Ultrasound-Guided Transbronchial Needle Aspiration. (7th April 2019) - Janssen, Katherine; Keenan, Joseph; Cho, Roy; Dincer, Erhan
Abstract : Endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) is now a standard of care to sample mediastinal lymph nodes and masses with high diagnostic accuracy and low complication rates. However, the procedure has potential complications that might be life-threatening. Here, we present the first case of Propionobacterium acnes ( P. acnes ) causing mediastinitis following EBUS-TBNA of a subcarinal lymph node.